Decreased expression of APAF-1 and increased expression of cathepsin B in invasive pituitary adenoma - Tanase, Cristiana (Onco Targets Ther, 2014)
PURPOSE: Apoptotic protease-activating factor-1 (APAF-1) and cathepsin B are important functional proteins in apoptosis; the former is involved in the intrinsic (mitochondrial) pathway, while the latter is associated with both intrinsic and extrinsic pathways. Changes in the expression of apoptosome-related proteins could be useful indicators of tumor development since a priori defects in the mitochondrial pathway might facilitate the inception and progression of human neoplasms. Our aim was to evaluate the profiles of APAF-1 and cathepsin B in relation with other molecules involved in apoptosis/proliferation and to correlate them with the aggressive behavior of invasive pituitary adenomas. MATERIALS AND METHODS: APAF-1 and cathepsin B were assessed in tissue samples from 30 patients with pituitary adenomas, of which 16 were functional adenomas and 22 were invasive adenomas. RESULTS: A positive relationship between high proliferation and invasiveness was observed in invasive pituitary adenomas when compared to their noninvasive counterparts (Ki-67 labeling index – 4.72% versus 1.75%). Decreased expression of APAF-1 was recorded in most of the invasive adenomas with a high proliferation index, while the cathepsin B level was elevated in this group. We have noticed a negative correlation between the low level of APAF-1 and invasiveness (63.63%; P<0.01); at the same time, a positive correlation between cathepsin B expression and invasiveness (59.09%; P<0.01) was found. In all, 81.25% out of the total APAF-1-positive samples were cathepsin B negative (P<0.01); 76.92% out of the total cathepsin B-positive samples were APAF-1-negative (P<0.01). These results were reinforced by an apoptosis protein array examination, which showed inhibition of the extrinsic apoptotic pathway in an invasive pituitary adenoma. CONCLUSION: A bidirectional–inverted relationship between APAF-1 and cathepsin B expressions was noticed. One might hypothesize that shifting the balance between mediators of cell death could result in changes in tumor behavior.